Assessment Levels of Depressive Symptoms among Hemodialysis Patients at Kirkuk General Hospital in Kirkuk City - Noori, Mustafa O.; Al-Ameri, Maan Hameed Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to assess levels of depressive symptoms among hemodialysis patients at Kirkuk general hospital in Kirkuk City. Descriptive design conducted at Kirkuk general hospital in Kirkuk city during the period of October 28th, 2019 to August 21th, 2020. Through a non-probability sample of (100) renal failure patients who experience hemodialysis were selected from Kirkuk general hospital, hemodialysis unit at Kirkuk city. The study showed that most of renal failure patients undergoing hemodialysis had sever level of depression. There is no significant association between level depression with patient’s age, gender, education level, occupation, residence, dialysis frequency, number hours, chronic disease, medication & duration of dialysis except marital status & monthly income, the researchers recommended to increase awareness level of patient’s & their families about the nature & type of renal disease & how minimize their distress that caused by the disease, as well provide psychological support for improve their psychological status, and training of nursing staff who work at hemodialysis unit on how handle with patients to help them decreased their depressive symptoms.